Dimethyl 5-amino-2,4,6-triiodoisophthalate - Zou, Pei (International Union of Crystallography, 2010)
The title compound, C(10)H(8)I(3)NO(4), crystallizes with two molecules in the asymmetric unit. The I atoms and the benzene ring plane in the two molecules are approximately coplanar, the I atoms deviating by −0.1631 (1), 0.0704 (1) and −0.0507 (1) Å from the mean plane of the benzene ring in one molecule and by 0.1500 (1), −0.0034 (1) and −0.1213 (1) Å in the other. The planes of the ester groups are almost orthogonal to those of the benzene rings in both molecules, forming dihedral angles of 83.5 (3), 76.4 (3), 97.3 (1) and 75.7 (1)°. The mean planes of the benzene rings in two molecules are inclined at 69.8 (3)° with respect to each other. In the crystal, intermolecular I⋯O interactions link the molecules into infinite chains. In addition, N—H⋯O and non-classical C—H⋯O hydrogen bonds are observed.